Traditional Chinese Medicine Targeting Heat Shock Proteins as Therapeutic Strategy for Heart Failure - Wang, Yanchun; Wu, Junxuan; Wang, Dawei; Yang, Rongyuan; Liu, Qing (Frontiers in Pharmacology, 2022)
Heart failure (HF) is the terminal stage of multifarious heart diseases and is responsible for high hospitalization rates and mortality. Pathophysiological mechanisms of heart failure include cardiac hypertrophy, remodeling and fibrosis resulting from cell death, inflammation and oxidative stress. Heat shock proteins (HSPs) can ameliorate folding of proteins, maintain protein structure and stability upon stress, protect the heart from cardiac dysfunction and ameliorate apoptosis. Traditional Chinese medicine (TCM) regulates expression of HSPs and has beneficial therapeutic effect in HF. In this review, we summarized the function of HSPs in HF and the role of TCM in regulating expression of HSPs. Studying the regulation of HSPs by TCM will provide novel ideas for the study of the mechanism and treatment of HF.